Ankle kinematics and kinetics during gait in healthy and rheumatoid arthritis post-menopausal women. (3rd April 2019) - Aleixo, P.; Vaz Patto, J.; Cardoso, A.; Moreira, H.; Abrantes, J.
Abstract: Objective: In the literature, it is not clear whether rheumatoid arthritis (RA) post-menopausal women have different ankle biomechanical parameters than healthy post-menopausal women. This study aimed to compare the ankle kinematics and kinetics during the gait stance phase of RA post-menopausal women with age-matched healthy post-menopausal women. Materials and methods: A three-dimensional motion analysis system (9 cameras; 200 Hz) synchronised with a force plate (1000 Hz) was used to assess ankle kinematics and kinetics during barefoot walking at a natural and self-selected speed. A biomechanical model was used to model body segments and joint centres (combined anthropometric measurements and the placement of 39 reflective markers). Thirty-six women (18 RA post-menopausal women and 18 age-matched healthy post-menopausal women) performed 14 valid trials (comprising seven left and seven right footsteps on a force plate). Lower limb muscle mass was evaluated by an octopolar bioimpedance analyser. Results: RA post-menopausal women yielded a longer stance phase and controlled dorsiflexion sub-phase ( p < 0.001), higher dorsiflexion at the final controlled dorsiflexion sub-phase and lower plantar flexion at toe off ( p < 0.05), lower angular displacements ( p < 0.05), and lower ankle moment of force peak and ankle power peak ( p < 0.001). No intergroup differences were found in lower limb muscle mass. Conclusions: RA post-menopausal women yielded changes in ankle kinematic and kinetic parameters during the gait stance phase, resulting in a lower capacity to produce ankle moment of force and ankle power during the propulsive gait phase.